2021
DOI: 10.1097/rlu.0000000000003691
|View full text |Cite
|
Sign up to set email alerts
|

Incidental Finding of Hibernoma in Prostate-Specific Membrane Antigen PET/CT

Abstract: We reported the case of a 76-year-old man followed up since 2008 for a prostatic adenocarcinoma with pelvic and retroperitoneal nodes. He was initially treated by hormonotherapy with a good biological response. Twelve years after, he demonstrated an increased PSA level up to 10.2 ng/mL. He underwent a 68Ga-PSMA PET/CT, which shown an intense uptake by a left iliac extern mass, suspected of recurrence. The histology concluded in a hibernoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…We previously reported a case of hibernoma and a case of interstitial pneumopathy due to polyangiitis granulomata, both of which demonstrated a very intense uptake, suggesting that even nonneoplastic vasculature and inflammatory vasculature can show strong 68 Ga-PSMA-11 uptake. 51,52 For this study, we determined that it was judicious to perform 68 Ga-PSMA-11 PET/CT examinations 3 months after the end of the radiotherapy and 6 months after treatment with bevacizumab FIGURE 3. Patient P09 display concordant images, suggestive of postradiation-related remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported a case of hibernoma and a case of interstitial pneumopathy due to polyangiitis granulomata, both of which demonstrated a very intense uptake, suggesting that even nonneoplastic vasculature and inflammatory vasculature can show strong 68 Ga-PSMA-11 uptake. 51,52 For this study, we determined that it was judicious to perform 68 Ga-PSMA-11 PET/CT examinations 3 months after the end of the radiotherapy and 6 months after treatment with bevacizumab FIGURE 3. Patient P09 display concordant images, suggestive of postradiation-related remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…Using the PubMed database, we searched for "hibernoma retroperitoneal" and found nine cases of this tumor in the abdominal cavity. [2][3][4][5][6][7][8][9][10] To our knowledge, this is the second case report of laparoscopic surgery for hibernoma removal. The patient's short-term results demonstrated that laparoscopic surgery is a viable option for hibernomas (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Using the PubMed database, we searched for “hibernoma retroperitoneal” and found nine cases of this tumor in the abdominal cavity 2–10 . To our knowledge, this is the second case report of laparoscopic surgery for hibernoma removal.…”
Section: Discussionmentioning
confidence: 99%
“…Scarce reports have demonstrated increased FDG uptake within hibernoma due to the metabolic activity in brown fat cells 5–12 . Incidental 68 Ga-PSMA uptake was also reported 13 . Differentiation of benign and malignant entities based on a single SUV measurement at baseline PET/CT was not possible.…”
mentioning
confidence: 99%